High-sensitivity CRP may be a marker of HDL dysfunction and remodeling in patients with acute coronary syndrome - Xiaoyu Tang (Nature Portfolio, 2021)
Abstract In patients with coronary artery disease (CAD), further increasing the level of high-density lipoprotein (HDL) cholesterol (HDL-C) as an add-on to statins cannot reduce cardiovascular risk. And it has been reported that HDL functional metric—cholesterol efflux capacity (CEC) may be a better predictor of CAD risk than HDL-C. CEC measurement is time-consuming and not applicable in clinical settings. Thus, it is meaningful to explore an easily acquired index for evaluating CEC. Thirty-six CAD patients and sixty-one non-CAD controls were enrolled in this cross-sectional study. All CAD patients had acute coronary syndrome (ACS). CEC was measured using a [3H] cholesterol loading Raw 264.7 cell model with apolipoprotein B-depleted plasma (a surrogate for HDL). Proton nuclear magnetic resonance (NMR) spectroscopy was used to assess HDL components and subclass distribution. CEC was significantly impaired in CAD patients (11.9 ± 2.3%) compared to controls (13.0 ± 2.2%, p = 0.022). In control group, CEC was positively correlated with enzymatically measured HDL-C levels (r = 0.358, p = 0.006) or with NMR-determined HDL-C levels (NMR-HDL-C, r = 0.416, p = 0.001). However, in CAD group, there was no significant correlation between CEC and HDL-C (r = 0.216, p = 0.206) or NMR-HDL-C (r = 0.065, p = 0.708). Instead, we found that the level of high-sensitivity C-reactive protein (hsCRP) was inversely associated with CEC (r = − 0.351, p = 0.036). Multiple regression analysis showed that the hsCRP level was associated with CEC after adjusting other cardiovascular risk factors and HDL-C, although the association would not reach significance if adjusting for multiple testing. NMR spectroscopy showed that HDL particles shifted to larger ones in patients with high hsCRP levels, and this phenomenon was accompanied by decreased CEC. In patients with CAD, the level of HDL-C cannot reflect HDL function. The impaired correlation between HDL-C and CEC is possibly due to an inflammation-induced HDL subclass remodeling. These hypothesis-generating data suggest that hsCRP levels, a marker of acute inflammation, may associate with HDL dysfunction in ACS subjects. Due to the design limited to be correlative in nature, not permitting causal inference and a larger, strictly designed study is still needed.